2022
DOI: 10.1155/2022/3495504
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Feature Recognition Method of Cross-Border Financial Derivatives’ Transaction Based on Fuzzy Support Vector Machine

Abstract: The traditional identification methods of transaction risk characteristics mostly use the amount of profit and cost to complete the risk assessment. The conflict between the two will lead to low stability. Therefore, the identification method of transaction risk characteristics of transnational financial derivatives is proposed. The fuzzy support vector machine method is used to identify the risk characteristics of cross-border financial derivatives transactions and compensate the errors in the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In linear regression [29][30][31], the insensitive loss function of a certain precision is defined to satisfy ε ≥ 0 and relaxation factors ξ k ≥ 0ξ * k ≥ 0 and parameter C are introduced (penalty factor C meets C ≥ 0, indicating the degree of penalty for samples exceeding ε). e problem of the optimal hyperplane that is difficult to solve is transformed into an easy-toimplement quadratic programming problem.…”
Section: Linear Regression Model Of Support Vector Machinementioning
confidence: 99%
See 1 more Smart Citation
“…In linear regression [29][30][31], the insensitive loss function of a certain precision is defined to satisfy ε ≥ 0 and relaxation factors ξ k ≥ 0ξ * k ≥ 0 and parameter C are introduced (penalty factor C meets C ≥ 0, indicating the degree of penalty for samples exceeding ε). e problem of the optimal hyperplane that is difficult to solve is transformed into an easy-toimplement quadratic programming problem.…”
Section: Linear Regression Model Of Support Vector Machinementioning
confidence: 99%
“…Although the choice of the kernel function will lead to different prediction performances of the support vector machine, it is found that the selection of the kernel parameter has a more noticeable impact on the results in the practical application of the regression prediction of the support vector machine. In many cases, it plays a crucial role in the performance of the learning machine [ 28 , 30 ]. Many scholars have used random search algorithms to determine nuclear parameters.…”
Section: Support Vector Machine Kernel Function Selection and Paramet...mentioning
confidence: 99%